PENGARUH OFFERING DAN CITRA PERUSAHAAN TERHADAP MINAT KERJA SAMA KLIEN MQTV BANDUNG - Raden Nuruliah Kusumasari (J-IKA : Jurnal Ilmu Komunikasi Fakultas Ilmu Komunikasi Universitas BSI Bandung, 2014)
Abstrak - Tujuan dari penulisan ini adalah untuk mengetahui seberapa besar Kontribusi Offering dan Citra perusahaan terhadap minat kerjasama klien. Metode penelitian yang digunakan adalah metode kuantitatif yang didukung survey bersifat eksplanatori, analisis kuantitatif digunakan untuk memperoleh skor atau nilai dari variabel-variabel yang ada.teknik pengumpulan datanya adalah studi kepustakaan, observasi, wawancara dan penyebaran angket kepada responden. Teknik pengumpulan sampel menggunakan sampel jenuh, yang mana semua anggota populasi di jadikan sampel, dengan  jumlah sampel 53 orang yang termasuk klien MQTV Bandung. Berdasarkan hasil analisis peneliti bahwa masih kurangnya petugas Marketing Public Relation di MQTV yang ikut berperan serta dalam kegiatan Offering guna meningkatkan citra perusahaan seperti : pelayanan yang diberikan MQTV menjadi terbatas, harga yang ditawarkan dan sistem kerjasama fresh money yang ditawarkan MQTV Bandung masih belum sesuai dengan keinginan klien. Hal-hal yang ingin peneliti Rekomendasikan sebagai bahan masukan bagi pihak Marketing Public Relation MQTV, sebaiknya dilakukan penambahan staff Marketing Public Relation karena itu akan berpengaruh terhadap peningkatan pelayanan, harga jual produk yang ditawarkan dan sistem kerjasama  fresh money, semua itu harus sesuai dengan apa yang di harapkan klien. Banyak atau sedikitnya jumlah staff Marketing public relations sangat berpengaruh juga terhadap jumlah klien. Kata kunci : Offering, Citra Perusahaan, Kerjasama Abstract - Management  Qolbu Television is a private company engaged in the local broadcasters who are in the territory Bandung, the development of this company is interesting to study because researchers saw MQTV is the first local television program that has character Edutainment (dakwahtainment). It can not be separated from issues of various industry competition television station, for which the MQTV always meet the demands of communication in improving relations between the target audience and the MQTV, then MQTV aware of the importance of the role of Marketing Public Relations to provide information to clients through direct marketing activities is a tool to attract the clients working with MQTV. The purpose of this paper is to determine how much influence to the Offering and Corporate image collaboration client interests . The research method used was a survey supported the quantitative methods are explanatory , quantitative analysis is used to obtain the  scores  or  values  of  the  variables.  The  technical  data  collection  is  library  research  , observation , interviews and questionnaires to the respondents . Sample collection technique using saturated samples , which is where all members be made in the sampled population , with a sample of 53 people that includes clients MQTV Bandung . Based on the results of our analysis that the lack of Marketing and Public Relations officer in MQTV who participate in the Offering activities in order to improve the image of the company such as : services provided MQTV be limited , the price offered and partnerships offered fresh money MQTV Bandung still not liking clients . Things like researchers Recommend as an input for the Marketing and Public Relations MQTV , should be the addition of Marketing and Public Relations staff as it would affect the improvement of service , the selling price of the products offered and partnerships fresh money , all of it must be in accordance with what is expected client . A lot or a little amount Marketing public relations staff is also very influential on the number of clients .Keywords : Offering , Corporate Image , Cooperation